Beberapa Faktor Yang Berhubungan Dengan Fungsi Tiroid Pada Pasangan Usia Subur (PUS) di Kecamatan Kersana Kabupaten Brebes - Ratnasari Kusumawati; Suhartono Suhartono; Sulistiyani Sulistiyani (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background : Pesticide exposure on women who live in agricultural areas can cause health problems such as disruption of thyroid function. Pesticides can inhibit the binding of iodine by the body. Hypothyroidism can cause disturbances in female reproductive system, including disorders of puberty and menstruation, pre menstrual syndrome, sexual disfunction, birth defects and low birth weight infant. Goiter are usually be found in mountainous or highland areas but now mostly found in the lowlands. This is probably due to the exposure to heavy metals such as Pb, the use of hormonal contraceptives, and consumption of thiocyanate. The purpose of this study was to identify some factors associated with thyroid function on child bearing age woman in Kersana Subdistrict, district of Brebes Method : It was an observational research using cross-sectional design. Research was conducted in 4 villages namely Kemukten, Limbangan, Sutamaja and Kubangpari Kersana Brebes District. The subjects were 87 women. Data obtained from TSH, FT4 serum, Pb in blood, kholinesterase in blood, urinary iodine excretion, thiocyanate, measurement of nutritional status, the interview to find out the type of contraception used by couples. Data were analyzed using chi square test. Result : The results showed that there was no correlation between levels of kholinesterase, Pb in blood, urinary iodine excretion, urinary thiocyanate, the type of contraception, age and BMI with thyroid function on child bearing age woman in Sub district of Kersana. There was no association between exposure of pesticides and Hypothyroid cases occured in Kersana Sub district. It was recomended that women of childbearing need to reduce the adverse impacts of pesticides by using personal protective equipment in agricultural activities and improve health and clean living, and health department should monitor and regular inspection for kholinesterase levels in women of childbearing age who live in agricultural areas. Keywords : Pesticides expose, thyroid disfunction, child bearing age woman.